REVIEW FAKTOR DETERMINAN KERAGAMAN KONSUMSI PANGAN - Hardinsyah Hardinsyah (Jurnal Gizi dan Pangan, 2007)
Index of food intake diversity or dietary diversity reflects the nutritional quality of the diet; and it is associated with nutritional health outcomes. Understanding factors determine index of dietary diversity is important for improving nutritional-health status of the people.  However, no studies have been done to capture completely the determinant factors of dietary diversity. This journal article is intended to review the determinants factor of dietary diversity from studies done in both develop and developing countries at individual and household levels.  The results show that four studies analyzed the food data at individual level and the other four studies analyzed the food data at household level; and most of the studies were done in USA. Method of dietary diversity measurement and its statistical analysis varies among the studies. A few dietary diversity studies have investigated particular determinant factors with attention given to assessing nutrition knowledge and socio-demographic factors; and the others on economic and ecological factors.  The present review  suggested that the determinant factors of dietary diversity are nutrition knowledge, food preference, household size and composition, food availability and ecological factors, time availability for food preparation, and food purchasing power e.g. income, food expenditure and food prices. Based on this review a comprehensive conceptual framework and model of the determinant factors of dietary diversity could be developed.